Game and Digital Culture: A Study on Hay Day Game - Angeline, Mia (Humaniora, 2016)
Digital games are a commercial product developed and distributed by media companies and often uses characters or scenarios of movies, books, and comics. The digital game play comes from individual media consumption patterns. Playing digital games also offer experience and satisfaction based on interactive communication technologies and immersive gameplay. In this digital age, digital games became more social-based, which means they implement the need to invite friends on social media to come into play and help each other in the game. The problems of this study was to determine what factors make Hay Day popular among the players and to find out how Hay Day changing the social patterns interaction of the players. This study aims to look at the functions of digital games in the context of communication with relations in social media and why certain games can achieve very high popularity, while other games failed miserably. This research focuses on Hay Day. The method used is descriptive qualitative approach with case study method. Data collection is using interviews with players active in the game, as well as observation and literature studies. The results showed that a game may gain popularity if someone has a social media environment prior to play. Interactive concept, simulation, and fantasy game technology are also the reason Hay Day became very popular. The perception that the digital game player who formerly regarded as anti-social experience has shifted in the concept of digital game-based social bookmark. Players who have a lot of friends in games are seen as someone who has a lot of friends and a high social level. This is in line with the functions of a traditional game in Indonesian culture, where the region has a wide variety of games to be played together and motivate positive social interaction. Function of digital games also increased, other than playing the game as entertainment, but also now the game became one of the effective tools to convey the message to the public.